(untitled) (Journal of Sustainability and Environmental Management, 2023)
Land suitability assessments play a crucial role in determining optimal land use patterns to meet specific requirements, particularly in the context of forest restorations and plantations. However, there is a lack of studies reporting such assessments for mangrove rehabilitation and reforestation in the Philippines, leading to low survival rates (10-20%) due to improper site selection and site-species matching. This study aims to identify and narrow down suitable sites for mangrove growth in La Union Province, facilitating ground truthing for site selection and species matching. The Geographic Information System (GIS) method, specifically the Weighted Linear Combination (WLC) using ArcMap software, was employed. The study identified four suitable sites along the coastline of La Union within the jurisdictions of Aringay, Bangar, Sto. Tomas, and the City of San Fernando, all actively involved in mangrove conservation. However, mangrove planting efforts in other municipalities along the coastline of La Union, such as Agoo, Balaoan, and Bauang, were not reflected on the maps due to data resolution limitations. Nevertheless, the study’s findings should be regarded as a supportive tool in the site determination process, with ground truthing and assessment remaining essential. Integrating the study’s results with mangrove rehabilitation/reforestation efforts offers efficiency options that have the potential to enhance project success rates.